The Effect of Alma Relationship Implementation On Sharia Bangking In Indonesia - Intan Amalia Qur'anna; Rahmawati Khoiriyah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This study aims to determine the effect of Asset Liability Management on the financial performance of Sharia Commercial Banks in 2017-2022. Asset Liability Management is the activity of optimizing the balance sheet structure of Islamic banks with various alternatives available to maximize profits while limiting risk to a minimum. The research method used in this study is quantitative, with multiple linear regression analysis using analytical methods with the help of the SPSS program, tests carried out such as regression tests and classical assumption tests with exogenous variables, namely Asset Liability Management and endogenous variables are financial performance. This research takes data from the annual financial statements of Islamic Commercial Banks, data obtained from the website of the Financial Services Authority in the financial statements for the year at Islamic commercial banks for the 2017-2022 period. In determining the sample used is purposive sampling, namely the determination of samples based on criteria, namely banking companies registered with Sharia Commercial Banks during 2017-2018. This study found that ALMA on the CAR and FDR variables had no effect on Financial Performance on the ROA variable. Meanwhile, NIM affects Financial Performance on the ROA variable. Application of ALMA to financial performance. The results of data processing show that CAR has no effect on ROA with a significant value of 0.165 and NIM has an effect on ROA with a significant value of 0.022 while FDR has no effect on ROA with a significant value of 0.135.